Comparing the Effectiveness of Cognitive Rehabilitation, Neurofeedback, and Their Simultaneous Use in Emotional Memory and Emotion Regulation in People with Stroke - Tayebeh Mousabeygi; Hossein Zare; AliAkbar Sharifi; Mahnaz Aliakbari dehkordi (Complementary Medicine Journal of Faculty of Nursing and Midwifery)
Introduction: Stroke is one of the most common and debilitating neurological diseases in adults. Defects in emotional memory and emotion regulation are prominent features of people with stroke. Therefore, the existence of an accessible and affordable treatment method to reduce the problems of people with stroke is required. The present study aimed to compare the effect of cognitive rehabilitation, neurofeedback, and the combination of both on emotional memory and emotion regulation in people with stroke. Methods: The research was carried out as a quasi-experimental study. The statistical population included 45 stroke patients undergoing treatment at Imam Reza Hospital in Kermanshah who were selected by purposive sampling method. After signing an informed consent form, the patients were placed in three groups of 15 people using a simple random allocation method. Following that, they underwent cognitive rehabilitation treatment, neurofeedback, and a combination of the two for eight weeks, followed by a two-month follow-up. Data collection tools were the Emotion Regulation Questionnaire (2003) and the Emotional Memory Test (1995). The data were analyzed in SPSS software (version 24) using a two-way analysis of variance (ANOVA) and Bonferroni post hoc test at the significance level of 0.05. Results: The results demonstrated that the mean scores of emotional memory (Sig=0.007, F=3.339) and emotion regulation (Sig=0.023, F=5.833) in the treatment groups increased significantly in the post-test and follow-up. The results of comparing the means between the groups showed that the combination of cognitive rehabilitation and neurofeedback treatments was more effective in emotional memory and emotion regulation than each of the treatments alone (P<001). The partial ETA value indicated that approximately 13.1% of the variation in emotional memory and 21.7% in emotion regulation could be explained by the combination treatment. Conclusion: As evidenced by the obtained results, the combination of neurofeedback and cognitive rehabilitation can have a more effective and lasting effect on the improvement of emotional memory and regulation up to two months after treatment.